Fostering positive emotions and history knowledge with location-based augmented reality and tour-guide prompts. (December 2020) - Harley, Jason M.; Lajoie, Susanne P.; Tressel, Tara; Jarrell, Amanda
Abstract: There is a lack of theory-driven empirical research that evaluates outcomes of location-based augmented reality (AR) applications with the purpose of improving instructional design and use guidelines. The primary aim of this study was to compare the effectiveness of two historical reasoning guide protocols, one based on prior research by Harley and colleagues (2016a; the other an extension) while learners used a mobile AR app to learn about history. Learners reported significantly higher levels of enjoyment and curiosity from learning about history than using the app itself, though mean levels were high for both—in contrast to negative emotions. Results suggest that the new and extended historical reasoning guide protocol succeeded in fostering higher levels of knowledge than the former. Findings also revealed that learners reported significantly higher levels of task value after the guided tour compared to their pre-guided-tour responses. Implications and future directions are discussed. Highlights: Significantly higher levels of enjoyment and curiosity from learning about history than from interacting with the app. Learning outcomes significantly higher in the extended protocol than the previously developed one (high scores in both). Significantly higher levels of task value reported after the guided tour compared to learners' pre-guided-tour responses. Significantly higher levels of enjoyment from learning about the Arts Building than history learning in formal settings. Findings paint a coherent and optimistic picture regarding the use of mobile AR apps for teaching history.